A Comparison of Palliative Radiotherapy Between 20 Gy in 5 Fractions and 30 Gy in 10 Fractions in Superior Vena Cava Syndrome Due to Carcinoma of Lung (Community Based Medical Journal, 2023)
A quasi-experimental study was conducted to compare palliative radiotherapy between 20 Gy in 5 fractions and 30 Gy in 10 fractions in superior vena cava syndrome due to carcinoma of lung. This study was done in National Institute of Cancer Research and Hospital (NICRH), Dhaka, Bangladesh, from September 2017 to August 2018. A total of 60 patients were enrolled in the study – 30 in each group. In Arm A, patients received 20 Gy in 5 fractions in 1 week, while in Arm B, patients received 30 Gy in 10 fractions in 2 weeks. Every patient was evaluated routinely to see the treatment outcome and toxicities. The mean age of Arm-A was 57.53±5.5 years and that of Arm-B was 57.40±5.4 years. After treatment, improvement of symptoms (e.g., edema, venous distension, dyspnea) of SVCS was observed. After 1 month of radiotherapy, complete resolution of venous distension occurred in majority of the patients (73.3% vs. 80%) and partial resolution occurred in rest of them (26.7% vs. 20%) in arms A and B respectively. Most of patients showed complete resolution of edema (83.3% vs. 86.7%), while few had partial resolution (16.7% vs. 13.3%) in arms A and B respectively. Symptoms of SVCS did not recur in any of the patients of both arms. Performance status also improved in all patients. Assessment of tumor response at the last follow-up showed partial response in 66.7% patients of Arm-A and 73.3% patients of Arm-B. Stable disease was observed in 33.3% patients of Arm-A and 26.7% patients of Arm-B. None of the patients showed disease progression. Toxicities included dysphagia (26.7% vs. 33.33%), fatigue (23.33% vs. 20%), nausea and vomiting (16.67% vs. 20%) and skin reaction (16.67% vs. 13.33%) in Arm-A and Arm-B respectively. All of those toxicities were grade-1 and easily controlled. There was no statistically significant difference between two treatment groups in terms of palliation of symptoms of SVCS, tumor response and toxicities. To summarize, although tumor response was not much satisfactory, both 20 Gy in 5 fractions and 30 Gy in 10 fractions are equally effective radiotherapy regimens in palliation of symptoms of SVCS due to lung cancer with tolerable toxicities. Hence, 20 Gy in 5 fractions can be a reasonable treatment choice in a resource-poor country like Bangladesh.CBMJ 2023 January: Vol. 12 No. 01 P: 33-40